THE PATH TO WHOLENESS: LEADERSHIP AND SELF-DISCOVERY THROUGH JUNGIAN ARCHETYPES IN THE LION KING MOVIE (2019) - Althaaf Muhammad; Margawati, Prayudias (English Literature Department, Faculty of Economics, Law, and Humanities, 2025)
This article explores leadership transformation through the lens of Jungian archetype in the narrative of The Lion King (2019). The movie depicts the individuation journey of its main characters, especially Simba, as a representation of the Hero archetype. The objective of this paper is to analyze Simba's individuation journey in The Lion King (2019) through the lens of Jungian archetypes. Through an in-depth analysis of Simba's relationships with supporting characters such as Mufasa (Mentor), Scar (Shadow), and Nala (Anima), the findings of this research reveal how Simba's emotional and psychological journey reflects Jung's stages of individuation, namely the integration of aspects of the self to achieve psychological wholeness by applying qualitative descriptive method in extracting movie’s scene lines. The film's narrative also shows the dynamics of leadership transformation, where Simba moves from a figure who runs away from responsibility to a wise, responsible, and balance-oriented leader. By utilizing powerful symbolism, such as the confrontation with Scar and the return of balance in the Pride Lands, this article shows that individuation is not only important in self-development but also in establishing true leadership. The article conclude that this article mainly provides new insights into how Jungian theory can be applied in modern narrative analysis, particularly in the context of personal transformation and leadership.